Contemporary Encounters with Ancient Metaphysics - Johnson, Ryan J.; Greenstine, Abraham Jacob (Book collections on Project MUSE., 2017)
18 essays breathe new life into the classic problems of ancient metaphysics using contemporary continental materialisms and realisms. In this volume, leading philosophers address the varied, volatile and novel encounters between contemporary and antique thought. They reconceive and redeploy the problems of ancient metaphysics: one and the many, the potential and the actual, the material and immaterial, the divine and the world itself. Alongside these essays are three original and previously unpublished translations of texts by Gilles Deleuze, Pierre Aubenque and Barbara Cassin. Key Features. 15 original essays and three previously untranslated articles on topics of ancient physics and metaphysics by some of the leading contemporary philosophers and scholars Provides a space for the burgeoning continental materialist, realist and metaphysical readings of ancient philosophical problems and texts